2001
DOI: 10.1002/jnr.1063
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine triphosphate and diadenosine pentaphosphate induce [Ca2+]i increase in rat basal ganglia aminergic terminals

Abstract: Synaptosomal preparations from rat midbrain exhibit specific responses to both ATP and Ap(5)A, which stimulate a [Ca(2+)](i) increase in the presynaptic terminals via specific ionotropic receptors, termed P2X, and diadenosine polyphosphate receptors. Aminergic terminals from rat brain basal ganglia were characterized by immunocolocalization of synaptophysin and the vesicular monoamine transporter VMAT2 and represent 29% of the total. These aminergic terminals respond to ATP and/or Ap(5)A with an increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 27 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…We explored the interaction between dinucleotide receptor activation and the exocytotic release of other neurotransmitters. Using microfluorimetric Ca 2+ measurement techniques combined with immunocytochemical studies, we showed the presence of the dinucleotide receptor in aminergic terminals isolated from basal ganglia [23]. A specific receptor for diadenosine polyphosphates is also present in cholinergic terminals from rat midbrain as well as in GABAergic or glutamatergic terminals obtained from the same source.…”
Section: Overview Of Dinucleotidesmentioning
confidence: 97%
“…We explored the interaction between dinucleotide receptor activation and the exocytotic release of other neurotransmitters. Using microfluorimetric Ca 2+ measurement techniques combined with immunocytochemical studies, we showed the presence of the dinucleotide receptor in aminergic terminals isolated from basal ganglia [23]. A specific receptor for diadenosine polyphosphates is also present in cholinergic terminals from rat midbrain as well as in GABAergic or glutamatergic terminals obtained from the same source.…”
Section: Overview Of Dinucleotidesmentioning
confidence: 97%
“…Ap n As are involved in many other processes, including neurotransmission (15), apoptosis (16), and analgesia (17). Of note, Ap 4 A is used in hypoxia therapy in humans (18).…”
mentioning
confidence: 99%
“…These results suggest that, under the condition of fatigue, serotonergic and dopaminergic turnover in the synaptic terminals is not properly activated, and thus fatigue sensation and physical activity are insufficient. Because maintenance of synaptic transmission requires energy (Atwood et al, 1972;Nguyen et al, 1997), and stimulation of synaptic release and recycling of synaptic vesicles is induced through ATP receptors in the presynaptic aminergic terminals (Giraldez et al, 2001), insufficient serotonin and dopamine turnover in the synaptic terminals might occur due to reduced energy utilization in the brain of the rest-deprived, fatigued rats.…”
Section: Discussionmentioning
confidence: 99%